Analysis of trend and determinant factors of imported soybean in the period of 2003-2022 - Zikri, Irfan; Safrida, Safrida; Susanti, Elly; Putri, Risty Angelia (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2020)
The import of soybean is still a necessity for the Indonesian government to meet the gap between domestic demand and supply.  This paper aims to analyze the trends of soybean import and its contributing factors in Indonesia.  The study employs a descriptive analysis by using secondary data in the form of time series from 2003-2017.  Data analysis uses trends analysis and single equation model with Ordinary Least Square method.  The main finding shows the trends of soybean production are to follow a quadratic pattern, tends to decrease with an average 6.12% per year, while demand and import linearly tend to increase respectively with an average 3.30% and 3.03% per year in 2018-2022.  The projection of the production will increase 27,60% in 2018 from the previous year and will gradually continue to decline to 0.4 million tons in 2022. Meanwhile, domestic demand projects 3,3 million tons in 2018 will increase to 3.7 million tons, and import volume is 2.5 million tons in 2018 and will increase to 3.0 million tons by 2022.  The main factors contributing to the import partially are domestic production and demands and follow by the exchange rate, the national and international prices of soybeans.  Statistically shows the increasing every ton of production will affect to decrease 1,02 tons of import volume, and the increasing every ton of demand will increase 0.99 tons of import volume.  Thus, the import policy is still unable to stimulate domestic production to fulfill the increasing domestic demand.